Analysis Study Effect Of Surabaya's Northern Sea Tides On The Highway Drainage Channels (Case Study: Kedung Mangu Road, Sidotopo Wetan, Kenjeran, Surabaya) - Sumarno Sumarno; Atik Wahyuni (Journal of World Conference (JWC), 2020)
One of the roads that is still a subscription to flooding in Surabaya when it rains is on Kedung Mangu road. Besides being close to the northern coast of Surabaya, Kedung Mangu road channel edge is still very small and a lot of trash and sediment. In this study the authors used secondary Gumbel method using the data from relevant agencies and secondary of data from observations in the field. Reviews These rainfall of data include the data, the data pool of the data the tide and the dimensions of the existing channels and other auxiliary buildings. From the data and the calculation, the value of the average rainfall is 93.41 mm / day. Rainfall intensity 25-year period is 47.949 mm / hour. While the flood discharge plan is 174.859 m3 / h. Its existing discharge chute is 100 908 m3 / h. From the Data Obtained tide high tide value of 150 cm occurred on December 13, 2016 and to its Lowest ebb -130 cm occurred on January 25, 2016. Thet Type of Surabaya's northern sea tides is the mixed tide. From the calculation and analysis can be concluded that the more influential is the amount of rainfall and dimensions and road conditions in the channel Kedung Mangu. So as to cope with floods In These locations, the dimensions of the channel should be enlarged.